Meta-analysis of the effect of project-based learning on enhancing 21st century skills - Chusni, Muhammad Minan (IAIN Palangka Raya, 2023)
The research objective is to investigate the effect of project-based learning on improving 21st-century skills. The research method used is a survey with documentation techniques on journals available in Indonesia One Search, which is then analyzed by meta-analysis by calculating the effect size of each research variable. From the journal search results, 25 journals were obtained, consisting of 9 journals on critical thinking skills, 10 on creative thinking skills, and six on problem-solving skills. The research findings revealed that the effect of project learning on students' necessary skills was 88%, the impact of project learning on students' creative skills was 82%, and the effect of project learning on students' problem-solving was 92%.The research objective is to investigate the effect of project-based learning on improving 21st-century skills. The research method used is a survey with documentation techniques on journals available in Indonesia One Search, which is then analyzed by meta-analysis by calculating the effect size of each research variable. From the journal search results, 25 journals were obtained, consisting of 9 journals on critical thinking skills, 10 on creative thinking skills, and six on problem-solving skills. The research findings revealed that the effect of project learning on students' necessary skills was 88%, the impact of project learning on students' creative skills was 82%, and the effect of project learning on students' problem-solving was 92%.